Business English teachers’ perceptions of their professional role in a Hungarian business school - Sándor, Eszter (Working Papers in Language Pedagogy, 2017)
Since English has become the most frequently used lingua franca of the world of business, it is the responsibility of business schools to prepare students for conducting business both in English and in the mother tongue. Stakeholders need fresh graduates who can use English in a wide range of unpredictable situations, while legal requirements and school curricula still force teachers and students to learn English in order to be able to pass high-stake exams. This qualitative case study aims to explore and understand how three business English teachers in a Hungarian business school see their professional role and how they cope with the challenges of fulfilling curricular requirements on the one hand and meeting student and stakeholder demands on the other. The results show that the participating teachers consider the roles of creating a safe learning environment and offering emotional scaffolding the most important in order to be able to bridge the gap between what they are compelled to do and what they feel they should do.